Sunday

April 20, 2014

April 20, 2014

Posted by **Sira** on Tuesday, May 8, 2012 at 3:33am.

1. x+y+3z=7

2. 2x-4y+z=7

3. 3x+5y-4z=-6

- Algebra 2 -
**Steve**, Tuesday, May 8, 2012 at 4:54amone simple way is to substitute x #1 into #2 and #3:

2(7-y-3z) - 4y + z = 7

3(7-y-3z) + 5y - 4z = -6

which gives you

-6y -5z = -7

2y - 13z = -27

now we see 2y = 13z-27, so

-3(13z-27) - 5z = -7

-44z = -88

z = 2

so, y = (26-27)/2 = -1/2

and x = 7-(-1/2)-6 = 1/2

**Related Questions**

algebra - 1.what is the simplest form of the producy sqrt 50x^7y^7 * sqrt 6 xy^4...

Math: algebra 1 - 3. Which method would be the simplest way to solve the system...

math - Simplify as indicated. State at least one property of multiplication or ...

Math: Algebra - 1. Which method would be the simplest way to solve the system? ...

algebra - write in simplest form 1/10 / 1/4 they way you typed the problem ...

algebra/math - i know this is probably a really simple answer and i'm gonna want...

math - Simplify as indicated. State at least one property of multiplication or ...

math - Simplify as indicated. State at least one property of multiplication or ...

science - If you were to conduct an experiment on prayer and healing, what ...

Algebra II - I need to write a polynomial in SIMPLEST FORM having roots 2,-2 and...